Strategy to Block Interference from the Source Language (cognate signifiants) in Korean-Chinese Interpretation - Kim, Hye-Rim (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2006)
AbstractAlthough Korean and Chinese are not from the same family of languages, they have the common denominator of cognate signifiant that is, both languages can be written with the same methods of expression. In this case cognate signifiant means that both Korean and Chinese can be expressed in Chinese characters. There are many similarities in the visual and acoustic images of the two languages and for this reason cognate signifiant persistently intervenes in interpretation of one to the other.Therefore, the purpose of this study is to highlight through the analysis of case studies how cognate signifiant causes interference by hindering the extraction of meaning in Korean-Chinese interpretation, and to explore ways of increasing Korean-Chinese interpretation ability based on the results of such research.In order to approach this issue, recorded examples of incorrect interpretation resulting from interference caused by cognate signifiant will be analyzed from the perspective of interpretation studies, which places importance on the conveyance of meaning for the purpose of achieving communication. Based on the results of such research, strategies to effectively block interference resulting from cognate signifiant will be established.